2018
DOI: 10.1007/s00540-018-2516-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Duke Activity Status Index with cardiopulmonary exercise testing in cancer patients

Abstract: In summary, both the limits of agreement and bias between the measured and DASI-predicted pVO were substantial. The DASI-predicted pVO based on patient's assessment of their functional status could not be considered a reliable surrogate of measured pVO during CPET for the population of patients pending major cancer surgery and cannot, therefore, be used as a triage tool for referral to CPET centres for objective risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Our findings are similar to previous results obtained in small cohort studies (n¼50, abdominal surgery 12 ; n¼43, intracavity cancer surgery 13 ), in which the DASI was a reasonably sensitive and specific predictor of AT (!11 ml kg À1 min À1 : AUROC 0.767, 95% CI 0.630e0.994; P¼0.0002) and VO 2 peak (>15 ml kg À1 min À1 : AUROC 0.765, 95% CI 0.620e0.900; P¼0.002). 12 Owing to our larger sample size using the METS study dataset 14 our results have increased precision as reflected by the narrower CIs.…”
Section: Differences In Prior Literaturesupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are similar to previous results obtained in small cohort studies (n¼50, abdominal surgery 12 ; n¼43, intracavity cancer surgery 13 ), in which the DASI was a reasonably sensitive and specific predictor of AT (!11 ml kg À1 min À1 : AUROC 0.767, 95% CI 0.630e0.994; P¼0.0002) and VO 2 peak (>15 ml kg À1 min À1 : AUROC 0.765, 95% CI 0.620e0.900; P¼0.002). 12 Owing to our larger sample size using the METS study dataset 14 our results have increased precision as reflected by the narrower CIs.…”
Section: Differences In Prior Literaturesupporting
confidence: 91%
“…In the perioperative setting, a limited number of small studies report that the DASI has moderate correlation with the VO 2 peak (R 2 ¼0.2e0.45) as measured by CPET in patients undergoing intra-abdominal surgery. 12,13 The Measurement of Exercise Tolerance before Surgery (METS) study, 14 a large international multicentre study, compared the prognostic accuracy of subjective preoperative assessment, various tools measuring fitness (DASI and CPET) and pro-B-type natriuretic peptide to assess the composite primary endpoint of myocardial infarction or death within 30 days after major noncardiac surgery. The DASI score was associated with improved ability to predict the primary outcome of the composite of myocardial infarction or death within 30 days after surgery, whereas the other assessed tools, including CPET, had limited ability to do so.…”
mentioning
confidence: 99%
“…The Duke Activity Status Index (DASI) has previously shown modest correlation with peak oxygen uptake in patients undergoing intra-abdominal surgery for cancer. 34,35 The METS trial Incidence of use of biomarkers for preoperative risk assessment. This figure shows that albumin is most frequently used to assess nutrition.…”
Section: Exercise Assessment and Prehabilitationmentioning
confidence: 99%
“…They reported that the Dukes Activity Status Index, a questionnaire to assess fitness levels and estimate VO 2 peak, correlated poorly with CPET in pre-operative cancer patients and concluded that, contrary to our findings using TUG, they could not recommend Dukes Activity Status Index as a triage tool for CPET. 25 TUG in this context would provide an objective and easily quantifiable method of triaging such patients.…”
Section: Discussionmentioning
confidence: 99%